Seni Rupa Dalam Soft Power Diplomasi Indonesia Di Suriname - Tri Wahyudi; Putri Anggraeni; Ratih Pertiwi (JURNAL RUPA, 2022)
Using fine art practice as a tool of Indonesia’s soft power diplomacy in Suriname is one of the critical instruments in the practice of bilateral relations between the two countries. This can be seen when soft power diplomacy is defined as a means of diplomacy that contains elements of culture, value systems, or policies. Such effort, of course, has a positive impact on international relations between the two countries for cooperation in the economic, socio-cultural, and even trade between nations. Soft power diplomacy can be interpreted as an effort to organise diplomacy to attract attention to the international world and create a cooperative relationship to attract public attention through efforts by using various channels, one of which is cultural media. In this study, the author uses qualitative research methods using an explanatory “Case Study” theoretical approach. Thus, the results achieved in this study are how the state can see that art, which is part of the culture in Indonesia, can be a medium to bridge bilateral relations between the two countries, Indonesia and Suriname. Keywords soft power, diplomacy, fine art, Suriname